ANALYSIS OF SPECIES COMPOSITION AND DENSITY OF MANGROVES IN BORONG KALUKUA AND BONTO BAHARI, MAROS REGENCY - Rukminasari, Nita; Ainun, Nur; Alam, Jamaluddin Fitrah; Moka, Wilma Joanna Carolina (Jurnal Ilmu Kelautan SPERMONDE, 2025)
This study analyzed the composition and density of mangrove species in Borong Kalukua and Bonto Bahari in Maros Regency. The research method involved a field survey using purposive sampling in several observation plots. The data obtained were analyzed using a quantitative descriptive method to calculate the averages and standard deviations. The results showed that the mangrove density in Borong Kalukua was higher than that in Bonto Bahari, with average densities of 450 and 350 trees/ha, respectively. The standard deviation value showed variations in density between plots, with Borong Kalukua showing more significant variation than Bonto Bahari. Environmental factors and anthropogenic pressures are considered the primary causes of these differences. This study highlights the importance of conservation and rehabilitation efforts in maintaining the balance of mangrove ecosystems, particularly in areas subjected to higher environmental pressures.